Pengaruh Bimbingan Dan Konseling Dalam Mengatasi Rasa Kurang Percaya Diri Bagi Mahasiswa - Amaliyah Lubis, Hilda; Syaukani, Syaukani; Wahyuni, Sri (Pedagogik: Jurnal Pendidikan dan Riset, 2024)
The aimed of this study was to know the effects of counseling in overcoming the lack of confidence of students in the departement Islamic Education Guidance and Counseling 6th semester. The research methodology of this study used quantitative approach with the kind of research quasy experiment non-equivalent control group design. The research was done at UINSU Medan. The population of this research were the entire students at the department of Islamic Education Counseling and Guidance 6th semester. The samples of this research were chosen from class bkpi-1 as an experiment class and bkpi-2 as a control class. Tho total samples were 40 students.Result of the study showed that there is an influence of counseling guidance in overcoming the lack of confidence of thhe students at the department of Islamic Education Guidance and Counseling 6th semester. It was proved by the results of Pos-test. The value of control class students is (69.55) and the value of experimental class students is (80.45). Therefore, this researchs conclude that guidance and counseling have a positive and significant impact on students' confidence at the departement of Islamic Education Counseling and Guidance 6th semester: Based on the results of data analysis using simple linear regression tests that it is significant value of 0.05 where the value is less than 0.05 or T <0.05, and the value of regression coefficient of guidance and counseling is 1.621, and the So, it can be conclude that group guidance has a positive influence on confidence levels of the students.